2017
DOI: 10.1002/cssc.201700873
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Ring‐Opening Polymerization of Lactide: Liquid‐Assisted Grinding for the Green Synthesis of Poly(lactic acid) with High Molecular Weight

Abstract: Mechanochemical polymerization of lactide is carried out by using ball milling. Mechanical energy from collisions between the balls and the vessel efficiently promotes an organic-base-mediated metal- and solvent-free solid-state polymerization. Investigation of the parameters of the ball-milling synthesis revealed that the degree of lactide ring-opening polymerization could be modulated by the ball-milling time, vibration frequency, mass of the ball media, and liquid-assisted grinding. Liquid-assisted grinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 36 publications
2
64
0
Order By: Relevance
“…In the recent past it has been shown that for reactions, where the solubility of the reactants or products is an issue, mechanochemistry – a field which is currently gaining momentum – can be a promising workaround [1220]. It has already been established as a versatile tool for the synthesis of several porous materials [2129] and polymers [3042].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past it has been shown that for reactions, where the solubility of the reactants or products is an issue, mechanochemistry – a field which is currently gaining momentum – can be a promising workaround [1220]. It has already been established as a versatile tool for the synthesis of several porous materials [2129] and polymers [3042].…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of polymer science, mechanochemistry has often been used as a tool for the controlled chain scission of macromolecules containing mechanophores . However, there are examples that describe the use of mechanochemistry to facilitate polymer synthesis . An idea that has been investigated to a lesser extent is the use of mechanochemistry to facilitate post‐polymerization modification reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Choosing the right medium is important because it not only affects the iodocyclization/addition ratio,[4b] but also helps to minimize solubility constrains resulting from the onium salt intermediate. [5b], In recent years, ball milling techniques have facilitated the design of mechanochemical reactions in diverse areas of chemistry like organic, organometallic, inorganic, biocatalysis, and polymer chemistry , . Having the possibility to carry out solventless reactions and to overcome solubility restrictions are among the uppermost notable advantages of ball milling techniques.…”
Section: Introductionmentioning
confidence: 99%